The Effect of Learning Styles on Learning Outcomes of 4th Grade Elementary School Students - Erry Yusuf; Vera Yuli Erviana (International Journal of Learning Reformation in Elementary Education, 2022)
The main problem in this study is whether student learning styles influence the learning outcomes of fourth-grade students at SD Negeri Nogotirto. This type of research is quantitative or experimental research with a quasi-experimental design. The population in this study were fourth-grade students, and the sample of this study used a saturated sample using the total number of fourth-grade students at SD Negeri Nogotirto. Twenty-five students of class IVA and 25 students of class IVB. The instruments used in this study were a learning style questionnaire, pretest and posttest sheets of student learning outcomes. The results showed that the data analysis used descriptive and inferential analysis. The results showed that the inferential statistical analysis used the Independent sample t-test formula with the help of IBM SPSS Statistics 21 Software. The 2-tailed significance value was 0.043 <0.05, so based on the decision-making provisions, it can be concluded that H1 is accepted and H0 is rejected. It means that there is an influence of learning style on the learning outcomes of fourth-grade students of SD Negeri Nogotirto.